Cryoprotective effect of different glycerol concentrations on domestic cat spermatozoa - Villaverde, Ana Izabel S. Balbin [UNESP]; Fioratti, Eduardo G. [UNESP]; Penitenti, Marcimara; Ikoma, Maura R.V.; Tsunemi, Miriam H. [UNESP]; Papa, Frederico Ozanam [UNESP]; Lopes, Maria Denise [UNESP] (Elsevier, 2013)
Cryopreservation of spermatozoa is a pivotal tool in assisted reproduction, and studies aiming to establish optimal freezing/thawing protocols are essential to enhance sperm survival. The objectives of the present study were to (1) compare the cryoprotective efficiency of three different glycerol concentrations (3%, 5%, and 7%) on the basis of post-thaw sperm quality and (2) investigate whether the incidence of morphologically abnormal sperm in fresh samples is related to cryodamage sensitivity. Semen was collected from six tomcats using an artificial vagina (total 18 ejaculates). Each ejaculate was diluted using Tris-egg yolk-based extender (TEY), evaluated, equally divided into three aliquots, and rediluted using TEY with and without glycerol to achieve final concentrations of 3%, 5%, and 7%. Samples were loaded into 0.25 mL straws, equilibrated for 60 minutes at 5 °C, frozen, and then thawed at 46 °C for 12 seconds. Fresh and frozen-thawed samples were evaluated for sperm motion parameters (computer-assisted sperm analysis), plasma membrane integrity (PMI; propidium iodide and carboxyfluorescein diacetate), and DNA integrity (acridine orange). Plasma and acrosomal membrane integrity were assessed by flow cytometry (propidium iodide and fluorescein isothiocyanate-conjugated pea (Pisum sativum) agglutinin) immediately after thawing. Sperm motion parameters were also evaluated at 30 and 60 minutes of postincubation. For all treatment groups, cryopreservation significantly impaired the PMI and sperm motion parameters, except for straightness and amplitude of lateral head displacement. DNA integrity showed a slight reduction (P < 0.05) when 3% glycerol was used. The percentage of total motility, progressive motility, and rapid spermatozoa were significantly lower immediately after thawing and up to 60 minutes of incubation for the 3% glycerol group when compared with 5% and 7%. No difference (P > 0.05) was found for PMI, acrosome integrity, and DNA integrity among post-thaw groups. However, higher (P < 0.05) incidence of viable cells with reacted acrosome and dead cells with intact acrosome were observed with 7% and 3% glycerol, respectively. Percentage of morphologically abnormal spermatozoa in fresh sample was positively correlated with PMI only in the 3% glycerol group and negatively correlated with sperm motility in the 5% and 7% groups. In conclusion, the final concentration of 5% glycerol offered better cryoprotective effect for ejaculated cat sperm, and the relationship found between prefreezing sperm morphology and post-thaw sperm quality showed to be dependent on final glycerol concentration. © 2013 Elsevier Inc.
Keywords: Acrosome; Cryopreservation; DNA integrity; Plasma membrane; Sperm motion; Felis catus; Pisum sativum